Pengaruh Intensitas Penggunaan Media Sosial TikTok terhadap Prestasi Belajar Matematika Siswa MTs Generasi Z: The Influence of TikTok Social Media Usage Intensity on the Mathematics Learning Achievement of Generation Z MTs Students - Sri Mualima; Amin Harahap; Nurlina Ariani Harahap (ITScience (Information Technology and Science), 2026)
This study aims to analyze the relationship between the intensity of TikTok social media use and the mathematics learning achievement of MTs students in Social Arithmetic. This study uses a quantitative, ex post facto design, so the researcher does not provide direct treatment but rather examines phenomena that have occurred naturally. The study population comprised all seventh-grade students at MTs Raudlatul Uluum Aek Nabara, and samples were selected through purposive sampling, namely two groups based on TikTok usage intensity (high and low). Data collection was conducted using a questionnaire to assess the intensity of TikTok use and a test to measure mathematics achievement. Data analysis included normality tests, homogeneity tests, Independent-Samples t-tests, and effect size estimates using Cohen's d. The results showed a significant difference between the two groups (p = 0.007 < 0.05). The average score of students with low TikTok usage intensity (8.357) was higher than that of the high-intensity group (6). The effect size of 0.72 indicates that the difference falls in the moderate range, so it has practical meaning in the learning context. These findings suggest a relationship between the intensity of TikTok use and students' math achievement. The higher the intensity of TikTok use, the lower the student's math achievement tends to be. It is hoped that the results of this study will serve as a reference for educators and parents in managing students' social media use more wisely and effectively.